COMPARISON ANALYSIS OF FINANCIAL PERFORMANCE OF SHARIA BANK AND CONVENTIONAL BANKS 2015-2019 - Enny Arita; Ratnawati Raflis, (Malaysian Journal of Business and Economics (MJBE), 2022)
This study aims to compare the financial performance of conventional banking with Islamic banking for the 2015-2019 period by using financial ratios consisting of CAR, ROA, ROE, LDR, and BOPO. Based on the sample criteria, which have been determined, two groups of research samples were obtained, namely 10 conventional banks and 10 Islamic banks. The sample was taken using the purposive sampling method. The statistical analysis tool used to prove the hypothesis in this study was the independent sample t-test. Data analysis in this study was carried out using descriptive statistical techniques. Based on the results of the independent sample t-test, it shows that there is a comparison of banking financial performance consisting of CAR, ROA, ROE, LDR, and BOPO between conventional banks and Islamic banks with a significant value(0.000 < 0.5).